Exact Controllability of an Impulsive Semilinear System with Deviated Argument in a Banach Space. (15th July 2014) - Das, Sanjukta; Pandey, Dwijendra N.; Sukavanam, N.
Abstract : A functional differential equation with deviated argument coupled with impulsive conditions is studied for the existence and uniqueness of the mild solution and exact controllability of the system. The results are obtained by using Banach contraction principle andC 0 semigroup theory without imposing additional assumptions such as analyticity and compactness conditions on the generated semigroup and the nonlinear term. An example is provided to illustrate the presented theory.